Analisis kinerja keuangan dengan menggunakan rasio likuiditas - Risma Alitia; Sutrisno Sutrisno; Ni'matun Nafiah (Journal Industrial Servicess, 2022)
In its business process, the company involves investors as other sources of capital or company financial sources. Therefore, investors are unlikely to stick with companies that have poor financial performance conditions. The purpose of this study was to analyze the financial performance of PT Gajah Tunggal Tbk in 2017 to 2020 based on the liquidity ratio. The data used in the form of secondary data, namely the company's financial statements for the 2017-2020 period. Analysis of the data used is the liquidity ratio which consists of the current ratio, quick ratio, and cash ratio. The results obtained from the analysis of the liquidity ratio at PT Gajah Tunggal Tbk seen that the company's financial condition was not optimal. This is because of the three ratios used, only the current ratio and the fast ratio are in good condition. Meanwhile, the cash ratio is in poor condition. The reason is, the company still often runs a deficit in meeting its short-term debt. In future research, it should be analyzed with other ratios such as profitability and solvency ratios so that financial conditions can be analyzed more broadly.